Persuasive communication, business owner as a mentor to influence entrepreneurial students (BIS Humanities and Social Science, 2026)
Students have great potential for entrepreneurship. However, they are afraid to start entrepreneurship, so after graduation they are still unemployed. The role of a business mentor is very important in persuading students to become entrepreneurs. This study analyzes how business owners can use persuasive communication to convince students to become entrepreneurs. This research method uses a qualitative approach, using in-depth interviews with business owners as mentors and students who have started a business. Data analysis reveals persuasive communication strategies, such as building personal relationships, and providing guidance. Data analysis using triangulation and Nvivo. Research shows that persuasive communication carried out by business mentors can persuade students to become entrepreneurs with strategies such as storytelling, attracting emotions, building an entrepreneurial mindset. From the research, 4 models were obtained to build entrepreneurship, namely: 1). Entrepreneurial motivation, 2). Understanding the importance of entrepreneurship, 3). Choosing entrepreneurship as a profession, 4). Dare to become a new entrepreneur. Business owner persuasive communication can be used to persuade students to become entrepreneurs.